STIMULASI LAGU DALAM PENGEMBANGAN SENI ANAK USIA DINI - Wicy Elvi Septiani; Indra Yeni (JCE (Journal of Childhood Education), 2021)
This research is motivated by the importance of providing song stimulation in the development of early childhood arts, while in reality the provision of song stimulation by teachers in schools still limited due to the limited production of children's thematic songs. So that it takes the teacher's ability to create simple songs according to the thematic needs of learning. This study aims to provide the elements of children's songs, namely melody, harmony, rhythm, lyrics, and tempo. Type of research used is literature study. Data were collected by reviewing and reviewing several relevant reading sources, such as scientific journals and related reference books. Furthermore, the elements that must be considered in early childhood songs are analyzed. From the research, the results show that the lyrical elements of children's songs must be positive and simple, the range and jump of the melody is right, the use of basic harmony starts and ends with level I chords, the use of a 1/4 or 1/8 rhythm, and the tempo according to the impression of the song to be shown. Thus the teacher can continue to provide song stimulation in the development of early childhood arts.